Alcohol‐Induced Developmental Origins of Adult‐Onset Diseases. (2nd June 2016) - Lunde, Emilie R.; Washburn, Shannon E.; Golding, Michael C.; Bake, Shameena; Miranda, Rajesh C.; Ramadoss, Jayanth
Abstract : Fetal alcohol exposure may impair growth, development, and function of multiple organ systems and is encompassed by the term fetal alcohol spectrum disorders (FASD). Research has so far focused on the mechanisms, prevention, and diagnosis of FASD, while the risk for adult‐onset chronic diseases in individuals exposed to alcohol in utero is not well explored. David Barker's hypothesis on Developmental Origins of Health and Disease (DOHaD) suggests that insults to the milieu of the developing fetus program it for adult development of chronic diseases. In the 25 years since the introduction of this hypothesis, epidemiological and animal model studies have made significant advancements in identifying in utero developmental origins of chronic adult‐onset diseases affecting cardiovascular, endocrine, musculoskeletal, and psychobehavioral systems. Teratogen exposure is an established programming agent for adult diseases, and recent studies suggest that prenatal alcohol exposure correlates with adult onset of neurobehavioral deficits, cardiovascular disease, endocrine dysfunction, and nutrient homeostasis instability, warranting additional investigation of alcohol‐induced DOHaD, as well as patient follow‐up well into adulthood for affected individuals. In utero epigenetic alterations during critical periods of methylation are a key potential mechanism for programming and susceptibility of adult‐onset chronic diseases, with imprinted genes affecting metabolism being critical targets. Additional studies in epidemiology, phenotypic characterization in response to timing, dose, and duration of exposure, as well as elucidation of mechanisms underlying FASD‐DOHaD inter relation, are thus needed to clinically define chronic disease associated with prenatal alcohol exposure. These studies are critical to establish interventional strategies that decrease incidence of these adult‐onset diseases and promote healthier aging among individuals affected with FASD. Abstract : The Developmental Origins of Health and Disease (DOHaD) hypothesis proposes that insults to the milieu of the developing fetus program for adult onset of chronic disease states. Recent studies indicate that prenatal alcohol exposure correlates with adult onset of neuro‐behavioral, cardiovascular, endocrine, and nutrient homeostasis deficits, thus warranting further investigation of alcohol‐induced DOHaD and patient follow‐up well into adulthood for affected individuals. In utero alcohol‐induced epigenetic alteration is a key potential mechanism for programming and susceptibility of adult‐onset chronic diseases.